1980
DOI: 10.1111/j.1440-169x.1980.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Penetration and the Formation of a Fertilization Cone in the Common Carp Egg*

Abstract: Sperm penetration and the formation of a fertilization cone in the micropylar canal of the egg of the common carp were examined by electron microscopy. The overwhelming majority of inseminated eggs fixed without immersion in fresh water showed that the first spermatozoon had penetrated into the ooplasm before the cortical reaction had occurred, and in many cases had formed a fertilization cone to plug the micropylar canal. At this stage the sperm head was usually located at the base of the cone, and the tail p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 24 publications
4
51
0
1
Order By: Relevance
“…According to Kudo (1980), the micropyle channel in Cyprinus carpio allows the access to several spermatozoa, suggesting that the agglomeration of supernumerary spermatozoa in the perivitelline space is required as an additional mechanism to prevent polyspermy. Ginsburg (1961) confirmed the agglutination of spermatozoa in the micropyle channel of Salmo trutta and reported that, by removing the perivitelline fluid, polyspermy was achieved in this species since it would prevent the accumulation of supernumerary spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kudo (1980), the micropyle channel in Cyprinus carpio allows the access to several spermatozoa, suggesting that the agglomeration of supernumerary spermatozoa in the perivitelline space is required as an additional mechanism to prevent polyspermy. Ginsburg (1961) confirmed the agglutination of spermatozoa in the micropyle channel of Salmo trutta and reported that, by removing the perivitelline fluid, polyspermy was achieved in this species since it would prevent the accumulation of supernumerary spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…In the carp and the rose bitterling, a fertilizing spermatozoonattaches first to the membraneof the microvilli at the SES just beneath a micropyle (9,15). Membrane fusion between sperm heads and egg microvilli has begun within 10 sec postinsemination (14).…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the SES just beneath the micropyle varies among different species of teleosts (2,6,8,9,10,15). In cyprinid fishes, the SES has many microvilli in a circle coinciding with the inside diameter of the micropylar aperture (6,10,15).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that sperm entry into the micropyle is not random, at least in these fish. The morphology of sperm entry in fish eggs was reported first by Yamamoto (1952) in the flounder, followed by many others in various fishes using both light and electron microscopes (Brummett and Dumont., 1979;Kudo, 1980;Iwamatsu and Ohta, 1981;Yamamoto, 1981, 1987;Amanze and Iyengar, 1990;Iwamatsu et al, 1991;Yanagimachi et al, 1992;Iwamatsu et al, 1993).…”
Section: Introductionmentioning
confidence: 99%